2014
DOI: 10.1590/s0104-77602014000100017
|View full text |Cite
|
Sign up to set email alerts
|

In vitro establishment and multiplication of genotypes of Eucalyptus dunnii Maiden

Abstract: ABSTRACT:This study aimed at evaluating the effect of genotypes of Eucalyptus dunnii on in vitro establishment and also the influence of genotypes grown in different concentrations of (0, 0.25, 0.50, 0.75, and 1.0 mg L-1 ESTABELECIMENTO E MULTIPLICAÇÃO in vitro DE GENÓTIPOS DE Eucalyptus dunnii MAIDENRESUMO: Conduziu-se este trabalho, com o objetivo de avaliar o efeito de genótipos de Eucalyptus dunnii no estabelecimento in vitro e a influência de genótipos cultivados em diferentes concentrações de 6-Benzi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
4

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 4 publications
0
6
0
4
Order By: Relevance
“…As for phenolic oxidation, the percentages were considered low, despite the fact that these are mother plants with advanced ontogenetic age, from which higher oxidation values were expected. Phenolic oxidation has been a problem associated with the micropropagation of woody species, as reported in several studies with E. cloeziana (Oliveira et al, 2015), E. benthamii ( Brondani et al, 2012b;Baccarin et al, 2015), Eucalyptus dunnii ( Navroski et al, 2014), Corymbia citriodora × Corymbia torelliana and Corymbia torelliana × Corymbia citriodora (Souza et al, 2019b), which reported similar response.…”
Section: In Vitro Establishmentmentioning
confidence: 69%
“…As for phenolic oxidation, the percentages were considered low, despite the fact that these are mother plants with advanced ontogenetic age, from which higher oxidation values were expected. Phenolic oxidation has been a problem associated with the micropropagation of woody species, as reported in several studies with E. cloeziana (Oliveira et al, 2015), E. benthamii ( Brondani et al, 2012b;Baccarin et al, 2015), Eucalyptus dunnii ( Navroski et al, 2014), Corymbia citriodora × Corymbia torelliana and Corymbia torelliana × Corymbia citriodora (Souza et al, 2019b), which reported similar response.…”
Section: In Vitro Establishmentmentioning
confidence: 69%
“…The chemical substances in the medium also enhance the rate of genetic variation of the plant. Some changes occurred during planting or callus development stage (Kasim et al 2017;Navroski et al 2014). The longer culturing the plant in vitro could enhance the possibility of B I O D I V E R S I T A S 21 (1): 80-85, January 2020 82 somaclonal variation.…”
Section: Initiationmentioning
confidence: 99%
“…Genetics affected by hormone, however, the same hormone could show a different response for each species. Contamination rate and respond to phenolic compounds also differ (Navroski et al 2014). Genetic changes could happen on initiation stage.…”
Section: Initiationmentioning
confidence: 99%
“…ex Woolls, and E. urophylla have been germinated on sterile moistened filter paper prior to transfer to semi-solid media for shoot culture or callogenesis [85][86][87]. Anti-browning agents such as polyvinylpyrrolidone (PVP), ascorbate, and activated charcoal are sometimes added to the establishment medium to improve eucalypt explant survival [16,[88][89][90][91][92][93][94][95]. Antibiotics can also be used during establishment to reduce bacterial or fungal contamination.…”
Section: Establishment Of Aseptic Culturesmentioning
confidence: 99%
“…Media that use MS salts are usually supplemented with organic additives, including some that are constituents of MS medium (e.g., 500-555 µM myo-inositol, 1-6.25 µM thiamine-HCl, 4.06 µM nicotinic acid, 2.43 µM pyridoxine-HCl, and/or 26.64 µM glycine) and some that are not (e.g., 0.4 µM biotin and/or 0.2 µM calcium pantothenate). Other proliferation media for eucalypts have included woody plant medium (WPM) [94,97], JADS media [98][99][100], DKW medium [101], mixtures of MS and de Fossard nutrients [102], and MS basal salts with either White vitamins or B5 vitamins [85,87,90,103]. Shoot proliferation is performed in the light, usually on semi-solid medium containing 58.4 mM or 87.6 mM sucrose (Table A1).…”
Section: Shoot Culturementioning
confidence: 99%